Efficacy of different types of cognitive enhancers for patients with schizophrenia: a meta-analysis. (December 2018) - Sinkeviciute, Igne; Begemann, Marieke; Prikken, Merel; Oranje, Bob; Johnsen, Erik; Lei, Wan; Hugdahl, Kenneth; Kroken, Rune; Rau, Carina; Jacobs, Jolien; Mattaroccia, Silvia; Sommer, Iris
Abstract Cognitive impairment is a core feature of schizophrenia, which is predictive for functional outcomes and is, therefore, a treatment target in itself. Yet, literature on efficacy of different pharmaco-therapeutic options is inconsistent. This quantitative review provides an overview of studies that investigated potential cognitive enhancers in schizophrenia. We included pharmacological agents, which target different neurotransmitter systems and evaluated their efficacy on overall cognitive functioning and seven separate cognitive domains. In total, 93 studies with 5630 patients were included. Cognitive enhancers, when combined across all different neurotransmitter systems, which act on a large number of different mechanisms, showed a significant (yet small) positive effect size of 0.10 (k = 51, p = 0.023; 95% CI = 0.01 to 0.18) on overall cognition. Cognitive enhancers were not superior to placebo for separate cognitive domains. When analyzing each neurotransmitter system separately, agents acting predominantly on the glutamatergic system showed a small significant effect on overall cognition (k = 29, Hedges'g = 0.19, p = 0.01), as well as on working memory (k = 20, Hedges'g = 0.13, p = 0.04). A sub-analysis of cholinesterase inhibitors (ChEI) showed a small effect on working memory (k = 6, Hedges'g = 0.26, p = 0.03). Other sub-analyses were positively nonsignificant, which may partly be due to the low number of studies we could include per neurotransmitter system. Overall, this meta-analysis showed few favorable effects of cognitive enhancers for patients with schizophrenia, partly due to lack of power. There is a lack of studies involving agents acting on other than glutamatergic and cholinergic systems, especially of those targeting the dopaminergic system.